2015
DOI: 10.3390/su70810602
|View full text |Cite
|
Sign up to set email alerts
|

Water Table Control for Increasing Yield and Saving Water in Cranberry Production

Abstract: Abstract:Water table control has been successfully tested to improve the sustainability of water management in cranberry production. In the province of Québec (Canada), three sites were investigated to determine the optimum water table depth below soil surface (WTD) using three criteria: (1) increasing yield without decreasing fruit quality; (2) minimizing the amount of water needed by the sprinkler system; and (3) avoiding hypoxic stresses in the rhizosphere. Our results show that the final yield, the berry s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 24 publications
3
39
0
Order By: Relevance
“…The results of Pelletier et al (2015b) also suggested that cranberry yields may be highly sensitive to very small changes in WTD, with variations on the order of ±30 cm resulting in a 25% reduction in crop yield. The suspected cause of the 25% crop reduction was the plant's inability to set fruit from flowers, which was supported by a decrease from two to one berries per fruiting upright in response to a WTD increase from 60 to 75 cm (Pelletier et al 2015b). Moreover, higher yields were associated with improved fruit quality, including increases in sugar content (Brix), TAcy, total acidity (TA), and the Brix:TA ratio (a taste perception indicator), for a WTD of about 60 cm.…”
Section: Water Table Controlmentioning
confidence: 79%
See 4 more Smart Citations
“…The results of Pelletier et al (2015b) also suggested that cranberry yields may be highly sensitive to very small changes in WTD, with variations on the order of ±30 cm resulting in a 25% reduction in crop yield. The suspected cause of the 25% crop reduction was the plant's inability to set fruit from flowers, which was supported by a decrease from two to one berries per fruiting upright in response to a WTD increase from 60 to 75 cm (Pelletier et al 2015b). Moreover, higher yields were associated with improved fruit quality, including increases in sugar content (Brix), TAcy, total acidity (TA), and the Brix:TA ratio (a taste perception indicator), for a WTD of about 60 cm.…”
Section: Water Table Controlmentioning
confidence: 79%
“…In contrast to recent work, research conducted in the 1970s showed that values of WTD between 30 and 38 cm resulted in higher fruit yield compared with those between 38 and 46 cm (3 of 4 yr) and to WTD values between 46 and 54 (4 of 5 yr) (Eck 1976). Using water table control as the primary source of irrigation, which was supplemented with sprinkler irrigation applied after SWP values dropped to −7.5 kPa, the highest yields were obtained with a WTD of 60 cm (Pelletier et al 2015b). The results of Pelletier et al (2015b) also suggested that cranberry yields may be highly sensitive to very small changes in WTD, with variations on the order of ±30 cm resulting in a 25% reduction in crop yield.…”
Section: Water Table Controlmentioning
confidence: 99%
See 3 more Smart Citations